2000
DOI: 10.1093/qjmed/93.5.291
|View full text |Cite
|
Sign up to set email alerts
|

The burden of alcohol misuse on an inner‐city general hospital

Abstract: Alcohol consumption in the UK has been increasing steadily. We prospectively studied the burden on hospital services caused by overt alcohol misuse, in an inner-city hospital in north-west England. All Accident & Emergency (A&E) patients were assessed to determine whether their hospital attendance was alcohol-related, and whether this resulted in admission and/or generated new out-patient appointments. Over 2 months, 1915 patients attended A&E with alcohol-related problems, accounting for 12% of attendances; 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 14 publications
3
45
0
2
Order By: Relevance
“…Prospective studies using various methods have reported a rate of substance use comorbidity of between 8% and 30% in medical patients. 6,9,26,27,29,30 Thus, our rate of substance use disorders, although not derived in a prospective fashion with validated instruments, is consistent with prior reports.…”
Section: Discussionsupporting
confidence: 88%
“…Prospective studies using various methods have reported a rate of substance use comorbidity of between 8% and 30% in medical patients. 6,9,26,27,29,30 Thus, our rate of substance use disorders, although not derived in a prospective fashion with validated instruments, is consistent with prior reports.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have estimated that between 2% and 40% of ED presentations are either alcohol-related or have evidence of a coincident alcohol problem (Charalambous, 2002). These presentations are more likely to occur out of hours and on weekends (Pirmohamed et al, 2000), when fewer staff and resources are available. They are also more likely to display violence and aggression towards staff (Crilly et al, 2004;Jenkins et al, 1998) and to be admitted to hospital (O'Farrell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies, such as the National Alcohol Indicators Project in Australia, 5 have focused on data concerning admissions to hospital, which is a limitation considering that most alcohol-related conditions do not result in that outcome. 6,7 Sources of information on the effect of interventions include health surveys and administrative data, as well as information from police and criminal justice databases (Appendix 1, available at www .cmaj .ca /cgi /content /full /cmaj .110367 /DC1). 8 Administrative data include data on ambulance use or presentations to hospital.…”
Section: Assessing Harm Reduction For Young Peoplementioning
confidence: 99%